Risk Management Committees’ Characteristics and the Financial Performance of Deposit Money Banks (Dmbs) in Nigeria - Lamidi, Wasiu Adebayo; Adebayo, Aderemi Olalere; Olorede, Titilope Esther; Oyekanmi, Mukaila Oyesegun (The Journal of Accounting and Management, 2022)
This paper examines the characteristics of risk committees as well as their effects on the financial performance of deposit money banks (DMBs) in Nigeria. The study made use of secondary data gathered from the bank’s annual reports, and 13 deposit money banks were chosen as a sample using the purposive sample technique. The data was analysed using the panel regression approach. Using a fixed effect model, the study discovered that the size and independence of risk management committees have a negative impact on the financial performance of deposit money banks in Nigeria, while the size of the committees is insignificant. Gender diversity and meetings have been shown to have a positive impact on the financial performance of DMBs in Nigeria. This study suggested that more women be included on the risk management committee, as well as that more frequent meeting be held to facilitate this participation.